2018
DOI: 10.1103/physrevmaterials.2.085603
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic evidence of the connection between liquid-liquid transition and dynamical crossover in an ultraviscous metallic glass former

Abstract: Liquid-liquid transitions are interesting to many researchers since they occur in systems 19 as diverse as monoatomic liquids, multicomponent oxides and metallic glass-formers. In 20 some cases, the crossover is accompanied by changes in the dynamical properties, 21 although a direct microscopic evidence of this connection has not been reported so far. 22 By combining state-of-the-art synchrotron techniques, we followed the structure and 23 atomic motion during quasi-static cooling the Au49Cu26.9Si16.3Ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 50 publications
5
27
2
Order By: Relevance
“…The fit of atomic mobility data to the VFT equation delivers T 0 = 348 K, log  0 = − 18, and D* = 6.8 ± 0.2. The latter is characteristic of a fragile liquid (38,47) and is in agreement with the high-temperature liquid fragility for this glass former reported elsewhere (17,43). The temperature dependence of  associated with cooling ratedependent T f values from FSC experiments (star symbols) also exhibits super-Arrhenius behavior but with different parameters.…”
Section: Vitrification Kinetics By Means Of Fictive Temperature Detersupporting
confidence: 88%
See 1 more Smart Citation
“…The fit of atomic mobility data to the VFT equation delivers T 0 = 348 K, log  0 = − 18, and D* = 6.8 ± 0.2. The latter is characteristic of a fragile liquid (38,47) and is in agreement with the high-temperature liquid fragility for this glass former reported elsewhere (17,43). The temperature dependence of  associated with cooling ratedependent T f values from FSC experiments (star symbols) also exhibits super-Arrhenius behavior but with different parameters.…”
Section: Vitrification Kinetics By Means Of Fictive Temperature Detersupporting
confidence: 88%
“…S7). (43). Furthermore, characteristic time scales based on previous calorimetric enthalpy recovery studies (17) are reported with diamond symbols.…”
Section: Vitrification Kinetics By Means Of Fictive Temperature Determentioning
confidence: 99%
“…This crossover has been observed on Vit 1 in 2007, studying the liquid viscosity above Tm and around TBr+ [79]. The crossover at Tg  TBr- Tm has been recently observed in the fragile liquid Au49Cu26.9 Si16.3 Ag5.5 Pd2.3 [80] and cannot be observed in a strong liquid because TBr-= Tg. These crossovers could only occur when glass Phase 3 is formed by previous cooling the melt below Tg and further heating above Tg and Tm.…”
Section: Formation Of a Liquid Ordering At Homogeneous Nucleation Temmentioning
confidence: 89%
“…4 However, a growing number of systems are found to exhibit abnormal changes in viscosity with temperature as they undergo a transition from fragile to strong (F-S). [5][6][7][8][9][10][11][12][13][14] These transitions are associated with anomalies in multiple thermodynamic variables such as the heat capacity, expansion coefficient and compressibility. 7,15 In some cases the F-S crossover can be extremely sharp, indeed discontinuous, as in the case of Si 16 and models of water.…”
Section: Introductionmentioning
confidence: 99%